(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Nodular goiter is mostly a benign thyroid tumor. A change of frequency of nodular goiter in areas with sufficient iodine intake has been documented in several reports. However, contrary to common belief it may also be associated with autoimmunity is being observed recently by many investigators. Objectives: To observe association between thyroid autoimmunity and nodular goiter. Methods: This cross sectional study included two hundred cases and one hundred controls. Clinically suspected nodular thyroid patients were confirmed by USG. Selection of healthy control was done after exclusion of nodule clinically and by USG. Data were collected through a structured questionnaire. Results: Frequency of positive anti-thyroid antibodies was significantly higher in nodular goiter cases, when anti-TPO and anti-TG considered together (42.5% vs. 25.0%; ?2=8.792, p=0.003) as well as individually (anti-TPO: 37.0% vs. 20.0%; ?2=8.955, p=0.004 and anti-TG: 31.0% vs. 9.0%; ?2=17.861, p<0.001) in the patients with nodular goiter than that of control. Conversely, there was no statistical difference between STN and MNG for antibody status when considered together (41.lvs. 42.5%; ?2=0.093; p=0.769) or separately (for anti-TPO: 34.2% vs. 38.6%; ?2=0.374, p=0.648 and anti TG: 27.4% vs. 33.1%; ?2=0.698, p=0.431). Also there was no statistical disparity for frequency of positivity of the two antibodies in STN (p=0.359) and MNG (p=0.167). Conclusion: Significant number of nodular goiter cases was positive for anti-thyroid antibodies.